Ras Signaling Regulates Stem Cells and Amelogenesis in the Mouse Incisor - Zheng, X. (J Dent Res, 2017)
The role of Ras signaling during tooth development is poorly understood. Ras proteins—which are activated by many upstream pathways, including receptor tyrosine kinase cascades—signal through multiple effectors, such as the mitogen-activated protein kinase (MAPK) and PI3K pathways. Here, we utilized the mouse incisor as a model to study how the MAPK and PI3K pathways regulate dental epithelial stem cells and amelogenesis. The rodent incisor—which grows continuously throughout the life of the animal due to the presence of epithelial and mesenchymal stem cells—provides a model for the study of ectodermal organ renewal and regeneration. Utilizing models of Ras dysregulation as well as inhibitors of the MAPK and PI3K pathways, we found that MAPK and PI3K regulate dental epithelial stem cell activity, transit-amplifying cell proliferation, and enamel formation in the mouse incisor.